A Bibliometric Exploration into the Global Research Impact of China's Thousand Talents Brand - Allen, Ryan M; Allen, Yang L (Comparative & international higher education, 2022)
The Thousand Talents Plan was an ambitious government initiative to repatriate and/or recruit experts from the global Chinese diaspora, along with some non-Chinese experts. The plan has received much criticism from abroad, accusing it of taking advantage of the open international education sector and facilitating espionage. While the Thousand Talents Plan received the most international attention, it was just one of over 200 Chinese governmental talent recruitment plans, which we label broadly as the Thousand Talents Brand (TTB). Using bibliometric analysis from the Web of Science, we find that research connected to the TTB decreased following the recent outcry but was only roughly 1% of all Chinese research output at its peak in 2018. We also find that the research was mostly concentrated in the hard sciences, with relatively little in the social sciences. Our results show the research funded through the initiatives was most partnered with researchers from the Western powers, including connections to institutions with national security concerns. While the findings do illustrate a complex web of global research governance through international partnerships, they cannot alleviate scrutiny of the potential alignment between the TTB programs and sensitive sectors abroad.